Liver Damage in Systemic Lupus Erythematosus in Adolescents - L.F. Bohmat; N.S. Shevchenko; Ye.V. Matviienko (Zaslavsky O.Yu., 2015)
The objective of the study was to investigate the state of the liver in adolescents with systemic lupus erythematosus (SLE). As a result of examination of 48 patients with SLE aged 12-18 years, there were established incidence of liver damage (22.9 %), correlation of cytolysis with the degree of activity and clinical manifestations of the disease. Also, the incidence of the risk of fibrosis (27.3 %) and its possible presence in 9.1 % of adolescents in the onset of SLE were detected.